Midkine Prevents Calcification of Aortic Valve Interstitial Cells via Intercellular Crosstalk - Zhou, Qian; Cao, Hong; Hang, Xiaoyi; Liang, Huamin; Zhu, Miaomiao; Fan, Yixian; Shi, Jiawei; Dong, Nianguo; He, Ximiao (Frontiers in Cell and Developmental Biology, 2021)
Calcified aortic valve disease (CAVD), the most common valvular heart disease, lacks pharmaceutical treatment options because its pathogenesis remains unclear. This disease with complex macroenvironment characterizes notable cellular heterogeneity. Therefore, a comprehensive understanding of cellular diversity and cell-to-cell communication are essential for elucidating the mechanisms driving CAVD progression and for developing therapeutic targets. In this study, we used single-cell RNA sequencing (scRNA-seq) analysis to describe the comprehensive transcriptomic landscape and cell-to-cell interactions. The transitional valvular endothelial cells (tVECs) that is intermediate state during endothelial-to-mesenchymal transition (EndMT), could be a target to interfere EndMT progression. Moreover, matrix valvular interstitial cells (mVIC) with high expression of midkine (MDK) interact with activated valvular interstitial cells (aVICs) and compliment-activated valvular interstitial cells (cVICs) through MK pathway. Then, MDK inhibited VICs calcification were validated by Alizarin Red S staining, real time quantitative polymerase chain reaction (RT¬-qPCR), and western blotting assays in vitro. Therefore, we speculated mVICs secreting MDK prevent VICs calcification. Together, these findings delineate the aortic valve cells heterogeneity, underlining the importance of intercellular crosstalk and MDK, which may offer a potential therapeutic strategy as a novel inhibitor of CAVD.